2015
DOI: 10.3389/fpsyt.2014.00196
|View full text |Cite
|
Sign up to set email alerts
|

Psychomotor Retardation in Elderly Untreated Depressed Patients

Abstract: Background: Psychomotor retardation (PR) is one of the core features in depression according to DSM V (1), but also aging in itself causes cognitive and psychomotor slowing. This is the first study investigating PR in relation to cognitive functioning and to the concomitant effect of depression and aging in a geriatric population ruling out contending effects of psychotropic medication.Methods: A group of 28 non-demented depressed elderly is compared to a matched control group of 20 healthy elderly. All partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…2, measures 22-25 and 29-32 and Fig. S2B) along with poor olfactory function and slow gait, known correlates of depression (35,36), as well as voiding dysfunction (Fig. 2, measures 39, 43, and 53).…”
Section: Medical Model Health Classesmentioning
confidence: 99%
“…2, measures 22-25 and 29-32 and Fig. S2B) along with poor olfactory function and slow gait, known correlates of depression (35,36), as well as voiding dysfunction (Fig. 2, measures 39, 43, and 53).…”
Section: Medical Model Health Classesmentioning
confidence: 99%
“…Fine motor skills, on the other hand, are involved in fine movements such as writing and drawing. Previous research has applied drawing tasks in depressed subjects to reveal substantial fine motor retardation in patients with MDD [14-18]. Several studies have measured gross motor activity in psychiatric disorders by means of wrist actimetry [19, 20] and found lower gross psychomotor activity in depressed patients than in healthy controls [21-24].…”
Section: Introductionmentioning
confidence: 99%
“…Summarily, these studies have aimed to uncover the influences of depression on motor control in young adults, despite that some of them omitted the medication status of the sample 20,26 or were under medication 22 , which might have biased the intended behavior. To our knowledge, Beheydt, Schrijvers, Docx, Bouckaert, Hulstijn and Sabbe 27 were the only who demonstrated that unmedicated depressive older adults presented motor control impairments in comparison to their nondepressed peers. Promising results were observed as they revealed that the execution and initiation times were significantly impaired according to the manipulation of the cognitive load of a figure copying task 27 .…”
Section: Introductionmentioning
confidence: 80%
“…To our knowledge, Beheydt, Schrijvers, Docx, Bouckaert, Hulstijn and Sabbe 27 were the only who demonstrated that unmedicated depressive older adults presented motor control impairments in comparison to their nondepressed peers. Promising results were observed as they revealed that the execution and initiation times were significantly impaired according to the manipulation of the cognitive load of a figure copying task 27 . The distinction of motor control aspects, on the other hand, is extremely relevant to understand the issues related to the interaction between aging and depression since it can provide an indirect measure of different brain dysfunctions 28 .…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation